Pelatihan Pengisian SPT Tahunan Online Bagi Guru-Guru SMP Negeri 17 Kupang - Erika Feronika Br Simanungkalit; Ari Data; Rolens E. H. Riwu Manu; Yeheskiel Nggandung; Markus U. K. Yewang; Jacob Abolladaka; Asnat C. Bani Bili; Andri Paulus; Fernando Saragih (Universitas Nusa Cendana, 2023)
Abstract The implementation of PKM was motivated by the low understanding of teachers regarding income tax and teachers did not know how to fill out and report the Annual Income Tax Return for Individual Taxpayers using e-Filing. To overcome these problems, various solutions can be carried out. One solution that can be provided is to conduct an Online Annual Tax Return Filling Training for Teachers of SMP Negeri 17 Kupang. The results achieved from the implementation of the PKM include 1) There is an increase in teachers' understanding of Income Tax, 2) Teachers are able to fill out and report the Annual Income Tax Return for Individual Taxpayers by using e-Filing. Keywords: Annual SPT, Income Tax, Taxpayers, E-filing Abstrak Pelaksanaan PKM dilatarbelakangi oleh rendahnya pemahaman guru-guru mengenai pajak penghasilan dan Guru tidak tahu cara mengisi dan melaporkan SPT Tahunan PPh Wajib Pajak Orang Pribadi dengan menggunakan e-Filing. Untuk mengatasi permasalahan tersebut maka dapat dilakukan berbagai pemecahan masalah. Salah satu solusi yang dapat diberikan adalah melakukan sebuah Pelatihan Pengisian SPT Tahunan Online Bagi Guru-Guru SMP Negeri 17 Kupang. Hasil yang dicapai dari pelaksanaan PKM antara lain: 1)Adanya peningkatan pemahaman guru mengenai Pajak Penghasilan, 2)Guru mampu mengisi dan melaporkan SPT Tahunan PPh Wajib Pajak Orang Pribadi dengan menggunakan e-Filing. Kata Kunci : SPT Tahunan, PPh, Wajib Pajak, E-filing